2012
DOI: 10.1073/pnas.1205374109
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic interactions between Tgfb1 and genetic loci, Tgfbm2 and Tgfbm3 , determine susceptibility to an asthmatic stimulus

Abstract: TGFβ activation and signaling have been extensively studied in experimental models of allergen-induced asthma as potential therapeutic targets during chronic or acute phases of the disease. Outcomes of experimental manipulation of TGFβ activity have been variable, in part due to use of different model systems. Using an ovalbumin (OVA)-induced mouse model of asthma, we here show that innate variation within TGFβ1 genetic modifier loci, Tgfbm2 and Tgfbm3 , alters d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…This is illustrated by the large spectrum of clinical severity and disease manifestations in individuals with mutations in TGFβ signalling pathway genes 8,41,186 . Moreover, in mouse models of cancer, asthma and vascular development, outcomes of reduced TGFβ1 levels are strongly influenced by interacting genetic modifier loci 5,9,186,187 . It is therefore most rational, economical and safe to preselect patient populations before initiating anti-TGFβ drug treatment on the basis of surrogate markers of TGFβ involvement in the disease process (such as increased TGFβ ligand and P-SMAD levels, and specific disease characteristics) and contra-indications of possible adverse side effects (such as susceptibility to inflammation or certain vascular conditions).…”
Section: Challenges and Considerations For Tgfβ Blockadementioning
confidence: 99%
See 1 more Smart Citation
“…This is illustrated by the large spectrum of clinical severity and disease manifestations in individuals with mutations in TGFβ signalling pathway genes 8,41,186 . Moreover, in mouse models of cancer, asthma and vascular development, outcomes of reduced TGFβ1 levels are strongly influenced by interacting genetic modifier loci 5,9,186,187 . It is therefore most rational, economical and safe to preselect patient populations before initiating anti-TGFβ drug treatment on the basis of surrogate markers of TGFβ involvement in the disease process (such as increased TGFβ ligand and P-SMAD levels, and specific disease characteristics) and contra-indications of possible adverse side effects (such as susceptibility to inflammation or certain vascular conditions).…”
Section: Challenges and Considerations For Tgfβ Blockadementioning
confidence: 99%
“…TGFβ action is highly context-dependent and influenced by cell type, culture conditions, interaction with other signalling pathways, developmental or disease stage in vivo and innate genetic variation among individuals 5-9 . This makes the pathway a particular challenge for drug development.…”
mentioning
confidence: 99%
“…Other methods, such as the dynamic clamp, which creates ‘real-time’ biological–computer hybrid models, can be used to assess mutations in cardiac genes 70 , to facilitate direct translation of protein dysfunction into disease-relevant phenotypes 71 and to assess drug safety 72 . Although there are well-known reasons for caution relating to the accuracy of such models of complex biological systems, there is increasing optimism that useful models of many key processes are and will be possible 73 .…”
Section: Functional Evaluationmentioning
confidence: 99%
“…Thus, screening the individual genetic background as well as the tumor microenvironment will be highly beneficial for predicting patients’ responses to a TGF-β antagonist. The key players of the TGF-β signaling pathway are previous biomarkers such as TGFβR2, Smad2, and Smad4 by tumor biopsy or genetic analysis [59,60,61,62,63]. However, several reports showed that loss of TGFβR2 expression is associated with more aggressive tumor behavior and reduced survival in human lung adenocarcinoma and squamous cell carcinoma [64].…”
Section: Challenges In Current Cancer Therapy Targeting Tgf-β and mentioning
confidence: 99%